MotomiRs: miRNAs in Motor Neuron Function and Disease - Hawley, Zachary C. E.; Campos-Melo, Danae; Droppelmann, Cristian A.; Strong, Michael J. (Frontiers in Molecular Neuroscience, 2017)
MiRNAs are key regulators of the mammalian transcriptome that have been increasingly linked to degenerative diseases of the motor neurons. Although many of the miRNAs currently incriminated as participants in the pathogenesis of these diseases are also important to the normal development and function of motor neurons, at present there is no knowledge of the complete miRNA profile of motor neurons. In this review, we examine the current understanding with respect to miRNAs that are specifically required for motor neuron development, function and viability, and provide evidence that these should be considered as a functional network of miRNAs which we have collectively termed MotomiRs. We will also summarize those MotomiRs currently known to be associated with both amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA), and discuss their potential use as biomarkers.